EFEITO DA DEFICIÃŠNCIA DE POTÃSSIO SOBRE ALGUNS ASPECTOS METABÃ“LICOS EM FEIJOEIRO (ð˜—ð˜©ð˜¢ð˜´ð˜¦ð˜°ð˜ð˜¶ð˜´ ð˜·ð˜¶ð˜ð˜¨ð˜¢ð˜³ð˜ªð˜´ L.) - Gutierrez, Luiz E.; Crocomo, Otto J.; Basso, Luiz C. (REVISTA DE AGRICULTURA, 2020)
EFEITO DA DEFICIÃŠNCIA DE POTÃSSIO SOBRE ALGUNS ASPECTOS METABÃ“LICOS EM FEIJOEIRO (ð˜—ð˜©ð˜¢ð˜´ð˜¦ð˜°ð˜ð˜¶ð˜´ ð˜·ð˜¶ð˜ð˜¨ð˜¢ð˜³ð˜ªð˜´ L.)